Estado nutricional y hábitos alimentarios en indígenas embera de Colombia (2010)
ABSTRACT: To analyze food habits and nutritional status in indigenous people. Methodology: Study of prevalence of two communities with different patterns of food acquisition: dependency of rainforest resources (Tausig) and farmers with a degree of acculturation (Nusidó). The usual daily intake (24 hours recall and nutrient analysis) and nutritional status by anthropometry (height-age, height-weight andIMC) were studied. Ethnography of foods was undertaken. Results: the traditional dietary ideal (hunting, fishing and harvesting), is not sustainable due to the low productivity and the socio-economic conditions. The prevalence of deficiency in daily intake (Atausí> Nusidó) is high: energy 73¿2%,proteins 36,6%, folic acid34¿2%, calcium 93,0%, vitamin A 61,4% and zinc 75,7%. Chronic under-nutrition appeared in 68}) % (0-10 years), and short stature in 77,1% (10-19 years),overweight in 45% (adults). Both communities have greater under-nutrition than the national level and the community more dependent on forest (Atausí) has worse nutrition outcomes. Conclusion: Current dietary habits do not guarantee the coverage of food requirements and have influence on under nutrition, along with other factors that increase food insecurity of Embera indigenous compared to the general Colombian population.